Wabula Village Woven Fabric Craftswomen Group: Utilisation of E-Commerce technology innovation to increase product marketability - Sa'ban, L.M. Azhar; Maulana Wijaya, Andy Arya; Ardiansah Putra, Muhammad Rizal; Gufran, La (Lembaga Riset dan Inovasi Masyarakat Madani, 2025)
This community service activity was conducted in Wabula Village, Buton Regency, involving participants from the Wabula Village Weaving Women’s Group. The group possesses significant economic potential; however, they have not yet fully optimised the marketing and sales of their woven fabric products. The primary objective of this initiative was to introduce the use of e-commerce platforms to transition traditional face-to-face transactions into a faster and more efficient online system. The method employed in this activity consisted of socialisation and hands-on mentoring. As a result, participants received essential information and practical assistance related to e-commerce utilisation. Furthermore, this initiative served as a motivational platform, encouraging the weaving group to expand their market reach by using their newly created e-commerce accounts and continuously innovating their products to enhance the growth and sustainability of their businesses.